Cytokinin regulates apical hook development via the coordinated actions of EIN3/EIL1 and PIF transcription factors in Arabidopsis. (30th August 2021) - Aizezi, Yalikunjiang; Shu, Huazhang; Zhang, Linlin; Zhao, Hongming; Peng, Yang; Lan, Hongxia; Xie, Yinpeng; Li, Jian; Wang, Yichuan; Guo, Hongwei; Jiang, Kai
Abstract : Cytokinin elaborately regulates apical hook development via EIN3/EIL1 and PIFs to facilitate soil emergence and the dark-to-light transition of seedlings, enabling plants to acclimate to the ambient environment. Abstract: The apical hook is indispensable for protecting the delicate shoot apical meristem while dicot seedlings emerge from soil after germination in darkness. The development of the apical hook is co-ordinately regulated by multiple phytohormones and environmental factors. Yet, a holistic understanding of the spatial–temporal interactions between different phytohormones and environmental factors remains to be achieved. Using a chemical genetic approach, we identified kinetin riboside, as a proxy of kinetin, which promotes apical hook development of Arabidopsis thaliana in a partially ethylene-signaling-independent pathway. Further genetic and biochemical analysis revealed that cytokinin is able to regulate apical hook development via post-transcriptional regulation of the PHYTOCHROME INTERACTING FACTORs (PIFs), together with its canonical roles in inducing ethylene biosynthesis. Dynamic observations of apical hook development processes showed that ETHYLENE INSENSITVE3 (EIN3) and EIN3-LIKE1 (EIL1) are necessary for the exaggeration of hook curvature in response to cytokinin, while PIFs are crucial for the cytokinin-induced maintenance of hook curvature in darkness. Furthermore, these two families of transcription factors display divergent roles in light-triggered hook opening. Our findings reveal that cytokinin integrates ethylene signaling and light signaling via EIN3/EIL1 and PIFs, respectively, to dynamically regulate apical hook development during early seedling development.